FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Jan Tobias Krüger; Kay-Peter Hoyer; Jingyuan Huang; Viviane Filor; Rafael Hernan Mateus-Vargas; Hilke Oltmanns; Jessica Meißner; Guido Grundmeier; Mirko Schaper (Journal of Functional Biomaterials, 2022)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.